Increase of laccase activity during interspecific interactions of white-rot fungi - Baldrian, Petr (FEMS microbiology ecology, 2004)
White-rot fungi are of interest due to their ability to degrade lignin. Lignin-degrading enzymes such as laccase can also degrade xenobiotic compounds. The effects of interspecific interactions between white-rot fungi and other microorganisms on laccase activity was studied in laboratory cultures. Laccase activity in cultures of Trametes versicolor and Pleurotus ostreatus increased significantly after the introduction of soil fungi, bacteria and yeasts or after contact with nonsterile soil. Addition of Trichoderma harzianum to cultures of T. versicolor increased laccase activity more than 40 fold, whereas addition of other soil fungi or bacteria resulted in 2-25 fold increases and the addition of soil or soil extracts led to 10-15 fold increases. No laccase induction was detected after addition of heat or filter-sterilized microbial cultures, soil or soil extract. Increased decolorization of the synthetic dye Remazol Brilliant Blue R occurred in mixed cultures. When T. versicolor was cocultured with other soil microorganisms, the number of colony forming units of the other soil microbes decreased. This effect could not be shown to be caused by laccase. In 16 of 24 species of white-rot fungi tested, laccase increased following the addition of T. harzianum. The increase was only absent in species with no or low laccase production. Co-inoculation of P. ostreatus and T. versicolor resulted in an increase of laccase in the mixed culture.
Keywords: Laccase; regulace genové exprese u hub; anthrachinony; Colony Count, Microbial; regulace genové exprese enzymů; Soil Microbiology; Gene Expression Regulation, Fungal; Antibiosis; počet mikrobiálních kolonií; půdní mikrobiologie; Trametes; Pleurotus; lakasa; Gene Expression Regulation, Enzymologic; antibióza; Anthraquinones